Sejarah kedatangan masyarakat Bugis ke Tanah Melayu: kajian kes di Johor - Khazin Mohd Tamrin,; Nordin Hussin,; Nelmawarni,; Rahilah Omar, (Penerbit UKM, 2009)
For centuries, many Bugis have left their villages in search for a new life and settlements. In the Malay culture, such practice is called as merantau or pasompe in Bugis. The merantau activities have over time strengthened the historical ties, blood connections and cultural linkages between the Bugis community and the people on the Malay Peninsula. The migration of Bugis to the peninsula occurred as early as the Malacca Sultanate. During the seventeenth century, there were already settlements of the Bugis people in the Malay Peninsula. Large-group migration, however, only occurred during the British colonial period, particularly the last quarter of the nineteenth century. Their migration to Malaysia has persisted until the present day. Although the exact number of the migrants cannot be determined due to the lack of written and oral sources, the majority of them have settled in the Johor and Selangor states in Peninsular Malaysia. In Johor, their roles as jungle settlers and pioneers of new rural settlements are among the important aspects that form the historiography of Johor. Until today, their existence can still be observed in some settlements, which spread over a few kampongs within the Johor territories. Ever since their first arrival to the peninsula, the Bugis have not only successfully marked their name in the local history, but they have also made their presence much more prominent than that of other groups.